Critical reappraisal of neoadjuvant concurrent chemoradiotherapy for treatment of locally advanced colon cancer - Chen, Yen-Cheng; Tsai, Hsiang-Lin; Li, Ching-Chun; Huang, Ching-Wen; Chang, Tsung-Kun; Su, Wei-Chih; Chen, Po-Jung; Yin, Tzu-Chieh; Huang, Chun-Ming; Wang, Jaw-Yuan (PloS one, 2021)
Locally advanced colon cancer (LACC) is associated with surgical challenges during R0 resection, increased postoperative complications, and unfavorable treatment outcomes. Neoadjuvant concurrent chemoradiotherapy followed by surgical resection is an effective treatment strategy that can increase the complete surgical resection rate and improve the patient survival rate. This study investigated the efficacy and toxicity of concurrent chemoradiotherapy in patients with LACC as well as the prognosis and long-term clinical outcomes of these patients. From January 2012 to July 2020, we retrospectively reviewed the real-world data of 75 patients with LACC who received neoadjuvant concurrent chemoradiotherapy. The chemotherapy regimen consisted of folinic acid, 5-fluorouracil, and oxaliplatin (FOLFOX). The following data were obtained from medical records: patients' characteristics, pathologic results, toxicity, and long-term oncologic outcome. Of the 75 patients, 13 (17.3%) had pathologic complete responses. Hematologic adverse effects were the most common (grade 1 anemia: 80.0% and leukopenia: 82.7%). Conversely, grade 2 or 3 adverse effects were relatively uncommon (<10%). Pathologic N downstaging, ypT0, and pathologic complete responses were significant prognostic factors for patient survival. Multivariate analysis revealed that pathologic N downstaging was an independent predictor of patients' overall survival (P = 0.019). The estimated 5-year overall and disease-free survival rates were 68.6% and 50.6%, and the medians of overall and disease-free survival periods were 72.3 and 58.7 months, respectively. Moreover, patients with pathologic complete responses had improved overall survival (P = 0.039) and an improved local recurrence control rate (P = 0.042) but an unfavorable distant metastasis control rate (P = 0.666) in the long-term follow-up. The long-term oncologic outcome of patients with LACC following concurrent chemoradiotherapy is acceptable, and the adverse effects seem to be tolerable. Pathologic N downstaging was an independent prognostic factor for patients' overall survival. However, a large prospective, randomized control study is required to confirm the current results.